Screening of Vigna unguiculata (L.) WALP. accessions from Togo for their reaction to Callosobruchus maculatus F - Affram, E.I.; Adetimirin, Victor O.; Fatokun, C.; Boukar, O. (Asian Journal of Agriculture and Biology, 2022)
Post-harvest losses in cowpea are mostly caused by the infestation of Callosobruchus maculatus, a storage pest. It can cause up to 100% loss of untreated produce. Host Plant Resistance (HPR), an important component of integrated pest management, has potential for sustainable management of C. maculatus. The objective of this study was to assess a recently collected cowpea germplasm from Togo for resistance to C. maculatus. A total of 200 cowpea accessions from the five regions of Togo and five checks were screened for resistance to C. maculatus using a no-choice assay. The experiment was laid out in a completely randomized design (CRD) with three replications. Data were collected on average number of eggs laid (ANEL), average number of adult emergence (ANAE), number of holes per seed (NHPS), initial and final seed weight (ISW and FSW), median development period (MDP), percentage adult emergence (PAE), and percentage weight loss (PWL), and two indices of resistance computed viz. insect growth index (G.I.) and Dobie’s susceptibility index (DSI). Data collected were subjected to analysis of variance, Pearson’s correlation and stepwise multiple regression analysis. A total of 51 accessions were moderately resistant, among which RS009 and RP218 had the least DSI score. The remaining accessions (149) were susceptible. DSI was significantly correlated with ANAE, PWL and NHPS, and had a significant and negative correlation with MDP. The results of the stepwise multiple regression showed ANAE, PWL and MDP were the better predictors of cowpea bruchid resistance and accounted for 87.7% of the observed variation in DSI scores.